A View from the Bush: Space, Environment and the Historiography of Science - Evenden, Matthew (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2005)
AbstractThis paper examines the interdisciplinary connections among the history of science, historical geography and environmental history. Four approaches have shaped recent scholarship: a spatial approach developed primarily but not exclusively within the discipline of geography that emphasizes problems of space, place, location and circulation; second, a disciplinary approach which pursues histories of environmental disciplines; third, a science and change approach containing works which emphasize the role of science in environmental change; and fourth an eco-spatial approach which includes studies that seek to engage with and link historiographies of science, environment and spatiality. I argue that these approaches have created new connections between fields that should be fostered and extended.